“The Italian Job”: How Social, Family Cohesion, and the Church Have Helped Spare Italy from a Prescription Opioid Crisis - Lo Bianco G; Schatman ME (Journal of Pain Research, 2023)
Giuliano Lo Bianco,1 Michael E Schatman2,3 1Anesthesiology and Pain Department, Fondazione Istituto “G. Giglio”, Cefalù, Palermo, Italy; 2Department of Anesthesiology, Perioperative Care and Pain Medicine, NYU Grossman School of Medicine, New York, NY, USA; 3Department of Population Health - Division of Medical Ethics, NYU Grossman School of Medicine, New York, NY, USACorrespondence: Michael E Schatman, Department of Anesthesiology, Perioperative Care, and Pain Medicine, NYU Grossman School of Medicine, 550 1st Ave, New York, NY, 10016, USA, Tel +1 425-647-4880, Email Michael.Schatman@NYULangone.org